Shaping Human Science Disciplines Institutional Developments in Europe and Beyond - Fleck, Christian; Duller, Matthias; Karády, Victor; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book presents an analysis of the institutional development of selected social science and humanities (SSH) disciplines in Argentina, France, Germany, Hungary, Italy, the Netherlands, Sweden and the United Kingdom. Where most narratives of a scholarly past are presented as a succession of 'ideas,' research results and theories, this collection highlights the structural shifts in the systems of higher education, as well as institutions of research and innovation (beyond the universities) within which these disciplines have developed. This institutional perspective will facilitate systematic comparisons between developments in various disciplines and countries. Across eight country studies the book reveals remarkably different dynamics of disciplinary growth between countries, as well as important interdisciplinary differences within countries. In addition, instances of institutional contractions and downturns and veritable breaks of continuity under authoritarian political regimes can be observed, which are almost totally absent from narratives of individual disciplinary histories. This important work will provide a valuable resource to scholars of disciplinary history, the history of ideas, the sociology of education and of scientific knowledge.
Chapter 1: Introduction; Christian Fleck, Matthias Duller, Victor Karády -- Chapter 2: The Rise of the Social Sciences and Humanities in France: Institutionalization, Professionalization and Autonomization; Gisèle Sapiro, Eric Brun & Clarisse Fordant -- Chapter 3: Germany: After the Mandarins; Christian Fleck, Matthias Duller & Rafael Schögler -- Chapter 4: The Post War Institutional Development of the SSH in the UK; Marcus Morgan -- Chapter 5: Discipline and (academic) tribe: Humanities and the social sciences in Italy; Barbara Grüning, Marco Santoro & Andrea Gallelli -- Chapter 6: The Institutionalization of SSH disciplines in the Netherlands: 1945 - 2015; Rob Timans & Johan Heilbron -- Chapter 7: A Reversed Order: Expansion and Differentiation of Social Sciences and Humanities in Sweden 1945-2015; Tobias Dalberg, Mikael Börjesson & Donald Broady -- Chapter 8: Institutionalization and Professionalization of the Social Sciences in Hungary since 1945; Victor Karady & Peter Tibor Nagy -- Chapter 9: Arduous institutionalization in Argentina: expansion, asymmetries and segmented circuits of recognition; Fernanda Beigel & Gustavo Sorá -- Chapter 10: Concluding Remarks; Christian Fleck, Matthias Duller, Victor Karády.
Keywords: Sociology; Science -- History; Intellectual life -- History; Philosophy and social sciences; Education and state; Education, Higher; Sociological Theory; History of Science; Intellectual History; Philosophy of the Social Sciences; Education Policy; Higher Education